Analisis Pemahaman Pajak dan Keadilan Pajak Terhadap Kepatuhan Wajib Pajak Usaha Mikro dan Kecil di Kota Palembang - Rizki Fitri Amalia (Politeknik Ganesha Medan, 2020)
This study aims to determine whether the variable tax fairness and understanding of taxes can affect the taxpayer compliance of Micro and Small Enterprises in the city of Palembang. The theory used in this research is attribution theory. The population in this study were all Micro and Small Enterprises in the city of Palembang. The sampling technique uses purposive sampling. The data analysis technique used is multiple regression analysis used to determine the effect of tax fairness variables and understanding of taxes on tax compliance of Micro and Small Businesses in Palembang. The results obtained indicate that the tax fairness variable does not affect the taxpayer compliance of Micro and Small Enterprises in fulfilling the obligations of their tax, while understanding of taxes affects the taxpayer compliance of Micro and Small Enterprises in fulfilling the obligations of their tax